Attacking Brazil's Poverty : A Poverty Report with a Focus on Urban Poverty Reduction Policies, Volume 1. Summary Report - World Bank (Washington, DC, 2013)
The first central message of this report is that Brazil has over the last years achieved great progress in its social policies and indicators. The second central message is that poverty remains unacceptably high for a country with Brazil's average income levels. The worst remaining income poverty is mostly concentrated in the Northeast region, and in the smaller urban and rural areas. The third central message is that, with decisive action, Brazil can achieve ambitious targets for further improvements in social indicators, including the objective of reducing the rate of extreme income poverty by 50 percent by the year 2015. Poverty is a complex and multi-dimensional phenomenon. Recognizing the rich literature on poverty in Brazil, this report attempts a few specific contributions. First, it presents a new 1996 poverty profile with a breakdown by city size, incorporation of the imputed value of owned housing, and regional price deflators. Second, it provides analysis of the incidence of selected public social spending based on the 1996/7 "Pesquisa sobre Padroes da Vida (PPV)." Third, it selectively synthesizes other work on poverty in Brazil in order to present an overview of cross-sectoral comparisons of the effectiveness of policy interventions. Fourth, it provides suggestions and selective inputs for devloping a national poverty reduction strategy. The report updates a previous World Bank assessment (report no. 14323) and builds on earlier work on urban poverty strategy.